MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA MELALUI MODUL ION KESETIMBANGAN DALAM LARUTAN GARAM BERBASIS DISCOVERY LEARNING WITH TEKNIK PROBING PROMPTING - Fefri Perrianty; Tri Haryanti; Asyah Khoirunisak (STIKES Keluarga Bunda Jambi, 2020)
Abstract - This study aims to determine the improvement of student critical thinking based on discovery learning using modules that help investigate questions that encourage questions about solubility and solubility results. The research design used was the Non-Equivalent Post-test Group Design. The population in this study was students of class XI IPA SMAN 1 Pariaman academic year 2018/2019. The selection of sample classes is done by cluster purposive sampling technique. The sample in this study was class XI IPA 1 as the control class and XI IPA 2 as the experimental class. The experimental learning class uses modules based on discovery learning with techniques probing prompting, while the control class without using modules. The research instrument used was a test of the results of learning critical thinking questions. The results of the study show that module based discovery learning with techniques probing prompting can improve students' critical thinking skills, as evidenced by the average increase in posttest results. The results of testing for normality and homogeneity state that the critical thinking value of the two distributed samples is normal and homogeneous. Hypothesis test results obtained by GIS. (2-tailed) of 0.016 <0.05 means that the value of critical thinking learners who use modules is based on discovery learning by techniques probing prompting differ significantly.